2013
DOI: 10.1155/2013/302426
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Herbal Medicines for Cancer Patients

Abstract: Medicinal herbs and their derivative phytocompounds are being increasingly recognized as useful complementary treatments for cancer. A large volume of clinical studies have reported the beneficial effects of herbal medicines on the survival, immune modulation, and quality of life (QOL) of cancer patients, when these herbal medicines are used in combination with conventional therapeutics. Here, we briefly review some examples of clinical studies that investigated the use of herbal medicines for various cancers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
187
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(190 citation statements)
references
References 143 publications
(151 reference statements)
1
187
0
2
Order By: Relevance
“…Consequently, the mitigation of the liver damage caused by CP could be an important clinical downside to be resolved. The pharmacodynamic constituents from natural herbs in complementary and alternative medicine (CAM) have been thought to be the main target among the combat with CP-induced liver damage (Yin, Wei, Jian, & Yang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the mitigation of the liver damage caused by CP could be an important clinical downside to be resolved. The pharmacodynamic constituents from natural herbs in complementary and alternative medicine (CAM) have been thought to be the main target among the combat with CP-induced liver damage (Yin, Wei, Jian, & Yang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many years of clinical trials in China have shown that TCMs can modulate immune function and improve the quality of life of cancer patients, particularly for patients undergoing che-motherapy [4] . Most TCM formulas are mixtures of different natural compounds, which might function in different ways and target different molecular pathways [5] . An emerging approach in biomedical research, systems biology, is a systemlevel analysis that focuses on complex interactions within biological systems [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Natural agents and herbal products can enhance the actions and diminish the toxicity of conventional chemotherapeutic drugs [7]. Artemisia is one of the large and diverse genera of Asteraceae family with various important medicinally valuable essential oils and secondary metabolites [8].…”
Section: Introductionmentioning
confidence: 99%